2008
DOI: 10.3382/ps.2007-00356
|View full text |Cite
|
Sign up to set email alerts
|

Broiler Chick Thrombocyte Response to Lipopolysaccharide

Abstract: The effect of lipopolysaccharide (LPS) on the expression of proinflammatory cytokines, interleukin (IL)-1beta, IL-6, and IL-12 in broiler chick thrombocytes was investigated. At 4 wk of age, blood samples were collected, and isolated thrombocytes were incubated with LPS for 1 h. Ribonucleic acid was extracted from the cells to examine the expression of the proinflammatory cytokines using real-time reverse transcription PCR. It was found that expressions of IL-1beta, IL-6, and IL-12 in thrombocytes were unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
5
21
1
2
Order By: Relevance
“…Finally, there was no upregulation of TLR4 or of some of the downstream effectors of TLR4, such as IL-1␤, IL-8, and LITAF (in the resistant line only). This is in clear contrast with what has been reported for the acute phase, during which a massive recruitment of heterophils and macrophages has been observed (43) and the levels of expression of IL-8 and IL-1␤ have been shown to be increased in vitro and in vivo (5,11,17,36). Overall, this suggests that mechanisms responsible for resistance to infection and those involved in resistance to the carrier state are different.…”
Section: Discussioncontrasting
confidence: 73%
“…Finally, there was no upregulation of TLR4 or of some of the downstream effectors of TLR4, such as IL-1␤, IL-8, and LITAF (in the resistant line only). This is in clear contrast with what has been reported for the acute phase, during which a massive recruitment of heterophils and macrophages has been observed (43) and the levels of expression of IL-8 and IL-1␤ have been shown to be increased in vitro and in vivo (5,11,17,36). Overall, this suggests that mechanisms responsible for resistance to infection and those involved in resistance to the carrier state are different.…”
Section: Discussioncontrasting
confidence: 73%
“…In the current study, feeding ascorbic acid, β-glucan, and corticosterone did not cause observable effects on splenic expression of selected genes (IL-1β, IL-2, iNOS, TLR4, and TLR15). This observation is similar to the findings reported by Ferdous et al (2008), who observed no significant effects of diets containing vitamin C and corticosterone fed to chicks between 2 and 4 wk of age on expression of IL-1β and other proinflammatory genes in thrombocytes. Expression of IL-1β and IL-2 was not significantly changed after dietary vitamin E supplementation to chicks from 1 d to 4 wk of age (Leshchinsky and Klasing, 2003).…”
Section: Resultssupporting
confidence: 93%
“…They express the major histocompatibility complex II and co-stimulatory molecules CD40, CD80, and CD86 (Ferdous et al, 2008). In addition of being unconventional, these expressions resemble innate effector cells in function and have a unique role in affecting adaptive immunity in chickens (Scott & Owens, 2008).…”
Section: Effects Of Glycyrrhizic Acid On Productive and Immune Paramementioning
confidence: 99%